2020
DOI: 10.3390/insects11040211
|View full text |Cite
|
Sign up to set email alerts
|

Male-biased Adult Production of the Striped Fruit Fly, Zeugodacus scutellata, by Feeding dsRNA Specific to Transformer-2

Abstract: Sterile insect release technique (SIT) is effective for eradicating quarantine insects including various tephritid fruit flies. When SIT is used for fruit flies, it is challenging to remove females from sterile males due to oviposition-associated piercing damage. This study developed a sex transition technique by feeding double-stranded RNA (dsRNA) specific to a sex-determining gene, Transformer-2 (Zs-Tra2) of the striped fruit fly, Zeugodacus scutellata. Zs-Tra2 is homologous to other fruit fly orthologs. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Using chitin synthase gene A (SeCHSA) as the target gene, the growth and development of Spodoptera exigua larvae fed by E. coli containing dsRNA of SeCHSA was disturbed, and then the mortality rates in the 5th instar larvae increased signi cantly [43]. After either feeding or injecting dsRNA of the sex-determining gene Transformer-2 to Zeugodacus scutellata, the Transformer-2 gene were all silenced, and increased signi cantly the number of male among their offspring [44]. Through RNAi to the appendage terminal Distal-less (Dll) gene of D. magna, it was found that the appendage terminal was de cient [45].…”
Section: Discussionmentioning
confidence: 99%
“…Using chitin synthase gene A (SeCHSA) as the target gene, the growth and development of Spodoptera exigua larvae fed by E. coli containing dsRNA of SeCHSA was disturbed, and then the mortality rates in the 5th instar larvae increased signi cantly [43]. After either feeding or injecting dsRNA of the sex-determining gene Transformer-2 to Zeugodacus scutellata, the Transformer-2 gene were all silenced, and increased signi cantly the number of male among their offspring [44]. Through RNAi to the appendage terminal Distal-less (Dll) gene of D. magna, it was found that the appendage terminal was de cient [45].…”
Section: Discussionmentioning
confidence: 99%
“…RNAi is useful for studying gene function in insects. Microinjection and artificial diets are the primary methods used to deliver dsRNA 39–44 . For D. citri and other small insects, feeding on an artificial diet with added dsRNA is the most effective strategy 30,45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Results were plotted using Sigma plot 10.0. Means were compared by least squared difference (LSD) test of one-way analysis of variance (ANOVA) using PROC GLM of SAS program 75 , 76 and discriminated at Type I error = 0.05.…”
Section: Methodsmentioning
confidence: 99%